Czasopismo „Język Rosyjski” — wstępna charakterystyka (komunikat) - Śliwowska, Wanda (Przegląd Rusycystyczny, 2009)
ЖУРНАЛ „JĘZYK ROSYJSKI” („РУССКИЙ ЯЗЫК”) — ВСТУПИТЕЛЬНАЯ ХАРАКТЕРИСТИКА Резюме Статья представляет вступительный обзор темы „Журнал Język Rosyjski” — из истории польской руссистики. В ней указана основная проблематика и структура журнала, его сотрудники и редколлегии. Место, занимаемое этим журналом в про-шлом польской дидактической и научной периодики, предвещает более подробную его характеристику в будущем. „JĘZYK ROSYJSKI” („RUSSIAN LANGUAGE”) MAGAZINE — PRELIMINARY CHARACTERISTICS Summary The following article tries to summarize briefl y the magazine “Russian Language”, which was published in Poland between 1948–1990.The article describes the inner structure of the magazine and the contents, as well as editors and consultants.The importance in the history of Polish scientifi c publications makes this article a subject of further work by the author.